Pertanggungjawaban Pidana Rumah Sakit atas Kelalaian Perawat yang Mengakibatkan Tertukarnya Bayi yang Baru Dilahirkan dalam Perspektif Hukum Kesehatan di Indonesia - Yandriza, Yandriza; Arma, Diana (UNES Law Review, 2023)
The process of enforcing criminal law should be carried out for the nurse's negligence which resulted in the exchange of newborn babies, bearing in mind that criminal law aims to protect against crimes against body and life, especially since the main victim is a baby/child where everything must be done in the best interests of the child. child. The law does not always discuss several compensations, but must also discuss the "Right to Life, and the Right to Defend Life.